Stress Testing Corporate Governance - Sullivan, John D.; Muis, Jules; Montagnon, Peter; Duverne, Denis; Hashimi, Fuad; Bertin, Marcos E.J. (International Finance Corporation, Washington, DC, 2018)
This compendium looks at the development of corporate governance since the financial crisis and asks whether governance rules and practices have developed in a way that positions companies better to address systemic risk. The occurrence of spectacular corporate scandals since the crisis—Tesco, Toshiba, VW, and Wells Fargo, and the many institutions affected by the LIBOR scandal—suggests that the governance lessons have not been learned, certainly not universally. So we ask,What more needs to be done? How can investors, regulators, and the concerned publics beassured that the board of directors is, in fact, practicing good corporate governance? This compendium look at stress-testing governance from several angles: systemic risk in the financial system, risk at the individual corporate level, and the differentiated challenge as exists between companies with dispersed ownership, family ownership, controlling shareholders, and state ownership.